Current Detection Circuit in Multiple Parallel Connection Circuit of High-Power Semiconductor Modules - Katoh, Miyu; Nagasu, Masahiro; Suzuki, Sosuke; Inaba, Masamitsu; Ishikawa, Katsumi; 美夕, 加藤; 正浩, 長洲; 宗佑, 鈴木; 政光, 稲葉; 勝美, 石川 (Denki Gakkai ronbunshi. D, Sangyō ōyō bumonshi, 2021)
We are developing current-detection technology that directly measures the main current of a high-power semiconductor module using the wiring inductance of the module. In a previous study, we proposed a circuit that detects current by integrating the voltage generated in the wiring inductance between the sense emitter and emitter terminals of the IGBT (Insulated Gate Bipolar Transistor) module. In this study, we developed a total current detection scheme for parallel-connected modules. The basic principle of this scheme is that the total current can be obtained by the total of each voltage generated on the wiring inductance of each module. It was realized by using only one integrating circuit. A challenge for this study was avoiding reflection caused by impedance mismatch. We addressed this by adding a termination resistance with the same value as the characteristic impedance.